2014
DOI: 10.1002/dneu.22158
|View full text |Cite
|
Sign up to set email alerts
|

Identification of initially appearing glycine‐immunoreactive neurons in the embryonic zebrafish brain

Abstract: Glycine is a major inhibitory neurotransmitter in the central nervous system of vertebrates. Here, we report the initial development of glycine-immunoreactive (Gly-ir) neurons and fibers in zebrafish. The earliest Gly-ir cells were found in the hindbrain and rostral spinal cord by 20 h post-fertilization (hpf). Gly-ir cells in rhombomeres 5 and 6 that also expressed glycine transporter 2 (glyt2) mRNA were highly stereotyped; they were bilaterally located and their axons ran across the midline and gradually tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…By this same logic, it is unlikely that the glycinergic commissural local (CoLo) interneurons responsible for providing reflex inhibition to Mauthner cells during larval escape behaviors are the source of glycinergic inhibition to CoPAs since their axons span only one somite in length (Satou et al, 2009). A recent study by Moly et al (2014) showed that a small number of glycine immunoreactive neurons are present in the hindbrain and rostral somites of the spinal cord at 20 hpf, coinciding with the arrival of glycinergic inputs to spinal neurons (Saint-Amant and Drapeau, 2000). One class of spinal neurons, the pacemaker IC cells, is located exclusively in the rostral spinal cord (Mendelson, 1986), suggesting that this region may contain specialized neurons not present in more caudal regions.…”
Section: Discussionmentioning
confidence: 99%
“…By this same logic, it is unlikely that the glycinergic commissural local (CoLo) interneurons responsible for providing reflex inhibition to Mauthner cells during larval escape behaviors are the source of glycinergic inhibition to CoPAs since their axons span only one somite in length (Satou et al, 2009). A recent study by Moly et al (2014) showed that a small number of glycine immunoreactive neurons are present in the hindbrain and rostral somites of the spinal cord at 20 hpf, coinciding with the arrival of glycinergic inputs to spinal neurons (Saint-Amant and Drapeau, 2000). One class of spinal neurons, the pacemaker IC cells, is located exclusively in the rostral spinal cord (Mendelson, 1986), suggesting that this region may contain specialized neurons not present in more caudal regions.…”
Section: Discussionmentioning
confidence: 99%
“…In brain tissue, Gly is an important inhibitory neurotransmitter. Gly release by binding of the presynaptic membrane with postsynaptic membrane receptors increases the permeability of the postsynaptic membrane to K + and Cl -, which hyperpolarises the postsynaptic membrane and produces an inhibitory postsynaptic potential, leading to the production of inhibitory action potentials by postsynaptic neurons (17,18). Excess Asp levels can activate its receptors, which can lead to excitatory neurotoxicity in the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…The antisera in this study have been widely and successfully used previously in zebrafish to identify and describe the transmitter phenotype of neurons (anti-ChAT: Berg et al, 2018;Clemente et al, 2004;Mueller et al, 2004;Moly et al, 2014;Ohnmacht et al, 2016;Reimer et al, 2008;anti-GABA: Berg et al, 2018;Djenoune et al, 2017;Higashijima et al, 2004;Moly et al, 2014;Montgomery et al, 2016;Mueller et al, 2006;anti-Glycine: Berg et al, 2018;Moly et al, 2014;anti-Serotonin: Berg et al, 2018;Kuscha et al, 2012;McPherson et al, 2016;Montgomery et al, 2016;anti-TH: Ampatzis et al, 2008;Ampatzis and Dermon 2010;Rink and Wullimann, 2004;anti-DβΗ: Ampatzis et al, 2008), and the green fluorescent protein (anti-GFP: Barreiro-Iglesias et al, 2013;Böhm et al, 2016;Kuscha et al, 2012).…”
Section: Antibody Specificitymentioning
confidence: 99%